Comparison of lipid classes and fatty acid compositions of farmed and wild pacific oysters, Crassostrea gigas, in Nha Trang, Vietnam - Huong, Trinh Thi Thu (Vietnam Journal of Marine Science and Technology, 2020)
Lipid classes and fatty acid compositions of the farmed (F-C. gigas) and wild (W-C. gigas) pacific oysters, Crassostrea gigas, in Nha Trang, Vietnam were investigated for the first time. The results indicated that the lipid classes and fatty acid components of these oysters were insignificantly different. The total lipid of both studied oysters included six lipid classes, namely phospholipid (PL), sterol (ST), free fatty acid (FFA), triacylglycerol (TG), monoalkyldiacylglycerol (MADG), and hydrocarbon-wax (HW) in which TG and PL were dominated with the values of 48.4%, 41.8% for TG and 19.0%, 20.3% for PL in F-C. gigas and W-C. gigas, respectively. The fatty acids (FAs) content of F-C. gigas and W-C. gigas was similar. The saturated fatty acids (SFAs) content was 48.2% in total fatty acids (TFAs) of the F-C. gigas and 44.7% in TFAs of W-C. gigas, in which 16:0 was dominated in SFAs of both oysters with the value of 24.2% in F-C. gigas and 22.0% in W-C. gigas. The contents of monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs) were 18.3%, 20.5% for MUFAs and 31.7%, 34.7% for PUFAs respectively in F-C. gigas and W-C. gigas. These MUFAs compositions contained 16:1n-7, 16:1n-5, 18:1n-9, 18:1n-7, 20:1n-11, 20:1n-9 and 20:1n-7, among them fatty acids 16:1n-7 (7.2% in F-C. gigas, 6.3% in W-C. gigas) and 18:1n-7 (6.6% in F-C. gigas, 7.4% in W-C. gigas) were the main MUFAs. PUFAs in these two oysters consisted of long-chain n-3 and n-6 fatty acids, in which 20:5n-3 (EPA) and 22:6n-3 (DHA) were dominated with the values of 12.7%, 13.9% for EPA in F-C. gigas and 6.5%, 6.0% for DHA in W-C. gigas.